The LTR, v-src, LTR provirus in H-19 hamster tumor cell line is integrated adjacent to the negative regulatory region - Machon, O; Hejnar, J; Hájková, P; Geryk, J; Svoboda, J (Gene, 1996)
The tumor hamster cell line H-19 harbors a single copy LTR, v-src, LTR provirus that becomes permanently transcriptionally suppressed in morphological revertants segregating at high rate from this cell line. Our previous data document that the provirus suppression is mediated by epigenetic cell-regulatory mechanisms. In this report, we concentrate on cellular sequences neighboring the integration site. The locus is unique for Syrian hamster and is not detectable in DNA of several animal species. No restriction sites that usually hint at the presence of CpG islands were found in the significantly close vicinity of the provirus. Nevertheless, the chromosomal DNA flanking the provirus is rich in GC content (57.8%). We localized a 0.5-kb region downstream from the provirus that remarkably inhibits transcription in the transient expression assay and is effective both on the homologous RSV LTR promoter/enhancer and heterologous SV40 promoter. We propose that a cellular trans-acting factor is involved in the silencing of the reporter gene. Since this activity is comparable both in transformed and revertant cells, we speculate that this down-regulatory region makes the permissive integration locus prone to provirus silencing initiated by other fluctuating stimuli.
Keywords: křečci praví; Tumor Cells, Cultured; repetitivní sekvence nukleových kyselin; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; viry ptačího sarkomu; Avian Sarcoma Viruses; zvířata; křeček rodu Mesocricetus; nádorové buňky kultivované; DNA; proviry; sekvenční analýza DNA; Genes, src; aktivace transkripce; Mesocricetus; Repetitive Sequences, Nucleic Acid; Transcriptional Activation; DNA virů; DNA, Viral; integrace viru; Virus Integration; Cricetinae; Animals; geny src; Proviruses